Protective role of 3-oxypyridine derivatives in rats' steroid-induced osteoporosis associated with reduced oxidative stress and recovery of nitric oxide formation - A. P. Danilenko; K. S. Trunov; M. V. Pokrovsky; L. M. Danilenko; M. V. Korokin; O. S. Gudyrev; A. A. Khentov; N. P. Masalytina; I. A. Tatarenkova; A. V. Cherednichenko; E. V. Boeva; I. S. Koklin; et al. (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2023)
From the point of view of the mechanisms for the implementation of pathogenetic links in the development of steroid-induced osteoporosis considered in the paper, the increased risk of the oxidative stress in osteoblasts, as well as the development of the vessels endothelial dysfunction of the microcirculatory bloodstream in the bone tissue, are of particular interest. They lead to the impaired bone tissue trophism and progression of osteoporosis.The aim of the study was research of the osteoprotective effects of a 3-hydroxypyridine derivatives composition on the model of steroid-induced osteoporosis.Materials and methods. To model osteoporosis pathology, the animals (male Wistar rats) were injected with methylprednisolone (MP) at the dose of 5 mg/kg (intraperitoneally) every 5th day for 5 weeks. Аs a non-selective blocker of NO synthase, L-NAME was used at the dose of 25 mg/kg (intraperitoneally). Derivatives of 3-hydroxypyridine (hereinafter referred to as composition No. 1) were administrated at the dose of 50 mg/kg (per os) In all experimental groups, the level of microcirculation and the bone mineral density, as well as the analysis of histomorphological and biochemical samples, were assessed.Results. The study results showed that composition No. 1 (50 mg/kg) has an osteoprotective activity, effectively prevents a decrease in the level of the regional bone tissue microcirculation and in the development of an endothelial dysfunction. That makes it possible to increase the bone mineral density and to slow down the thinning of bone trabeculae. In addition, composition No. 1 (50 mg/kg) reduces the production of reactive oxygen species and increases the NO bioavailability.Conclusion. The data obtained indicate that the studied composition of 3-hydroxypyridine derivatives is considered a promising compound for the prevention and treatment of steroid-induced osteoporosis.